The Historical Jesus in Context - Crossan, John Dominic; Allison, Dale C., Jr., 1955-; Levine, Amy-Jill, 1956- (Book collections on Project MUSE., 2006)
The Historical Jesus in Context is a landmark collection that places the gospel narratives in their full literary, social, and archaeological context. More than twenty-five internationally recognized experts offer new translations and descriptions of a broad range of texts that shed new light on the Jesus of history, including pagan prayers and private inscriptions, miracle tales and martyrdoms, parables and fables, divorce decrees and imperial propaganda. The translated materials--from Christian, Coptic, and Jewish as well as Greek, Roman, and Egyptian texts--extend beyond single phrases to encompass the full context, thus allowing readers to locate Jesus in a broader cultural setting than is usually made available. This book demonstrates that only by knowing the world in which Jesus lived and taught can we fully understand him, his message, and the spread of the Gospel. Gathering in one place material that was previously available only in disparate sources, this formidable book provides innovative insight into matters no less grand than first-century Jewish and Gentile life, the composition of the Gospels, and Jesus himself.